The use of adwords on the internet as an infrigement of trademarks - Bardales Mendoza, Enrique (2017)
The aim of this paper is exposed, to light of a landmark like “Google France” case, as he has faced the course of trademark infringement through AdWords Service offered by the search engine Google via their Internet Web, what is the service and who is responsible for the use of the key to identify a business offering products or services in a web page words, which when referring to trademarks may incur infringement holders thereof.